An Improved Hybrid Method for Inverse Obstacle Scattering Problems (Communications in Mathematical Research, 2021)
An improved hybrid method is introduced in this paper as a numericalmethod to reconstruct the scatterer by far-field pattern for just one incident directionwith unknown physical properties of the scatterer. The improved hybrid method inherits the idea of the hybrid method by Kress and Serranho which is a combinationof Newton and decomposition method, and it improves the hybrid method by introducing a general boundary condition. The numerical experiments show the feasibilityof this method.